A Case Study for Integrating Ayurvedic Panchakarma Therapies for Management of Chronic Kidney Disease - Acharya Manish Ji; Gitika Chaudhary; Manjeet Singh; Richa (AYUSHDHARA, 2025)
Chronic Kidney Disease (CKD) is a global health issue which affects the structure and function of kidney, predominantly found with hypertension. The disease is divided into five stages based on glomerular filtration rate (GFR), but the identification of stage 1 and stage 2 CKD cannot be done with GFR alone because in those individuals the GFR may be normal or borderline normal. The management CKD requires a multidisciplinary treatment approach and regular monitoring because it is a slow progressing disease with no symptoms in the early stage. This case report focuses on a 42-year-old female patient with CKD stage 5 since 5 years and hypertension for 2 years who received Ayurvedic treatment at Jeena Sikho Lifecare Limited Hospital, Derabassi. The treatment method administered on her was a blend of personalized Ayurveda and Panchakarma therapies, resulting in significant progresses in her symptoms, kidney health and function, and general life quality. After 10 days of treatment, the patient showed improvement in GFR and reported relief from pain and other symptoms. The results of this study emphasize the potential of Ayurveda as an economical treatment method which can substitute the conventional treatments, especially for individuals with low financial background to acquire advanced healthcare. Even though the findings of the present study are promising, further studies incorporating larger randomized controlled trials must be done for the evaluation of these Ayurvedic interventions for CKD to ensure its efficiency and safety.